The effects of the affordable care act dependent coverage mandate on parents’ labor market outcomes - KIM (Institutional Knowledge at Singapore Management University, 2022)
We examine the labor market impacts of the Affordable Care Act dependent mandate (ACA-DM), which has significantly increased dependent children's health insurance coverage through parents’ employer-sponsored health benefits. Using data from the American Community Survey, we find that the ACA-DM reduced parents’ annual wages by about $2,600. However, the probability of employment and working hours only decreased marginally. The back-of-the-envelope calculation indicates that the magnitude of the estimated wage impact is similar to the increased insurance premium of a family plan due to the ACA-DM. These findings imply that a deadweight loss associated with the expansion of dependent health coverage is likely to be small as an increase in employers’ labor costs is offset by a reduction in parents’ wages without significant reductions in labor inputs.